THE MAGIC MOTIVE IN UZBEK LEGENDS (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
This article will look at the investigation of magical components in Uzbek legends such as "Xon–Atlas" and "Tower Kalon". The work's objective is to analyze how magic is used in Eastern mythology.